Detecção de fraudes em queijo de manteiga e em manteiga de garrafa do Rio Grande do Norte - Linhares, Manuella de Oliveira Cabral Rocha (2020)
Butter cheese and bottle butter are traditional products and widely consumed in Northeast Brazil. In addition, they have great relevance to the socioeconomic growth of the region. Most of these products are handcrafted by small producers in which inadequate hygiene practices and the addition of ingredients not permitted by law can be carried out. Thus, the objective was to evaluate the microbiological physico-chemical quality and the detection of possible fraud in butter cheeses and bottle butters sold in Rio Grande do Norte. For that, 30 samples of butter cheeses and 30 of bottle butters were acquired in cheese supermarkets, bakeries, street markets and on highways in Rio Grande do Norte. The samples were subjected to microbiological analyzes (Coliforms at 35 and 45 ºC Staphylococcus coagulase positive and Salmonella spp.) Physical-chemical (moisture fat pH chlorides acidity) Lugol test (only for cheese) and the fatty acid profile in gas chromatography. It was observed that 87% and 33% of the cheese and bottle butter samples, respectively, presented high counts for positive coagulase Staphylococcus. Only one cheese sample was present for Salmonella spp. In cheeses, average results were obtained for moisture of 43.79% fat 26.70% pH 4.81 chlorides 8.07% and acidity 1.53%. For butter, average results were obtained for moisture of 0.28% fat 98.38% non-greasy solids 1.34% pH 4.65 chlorides 0.05% total solids 99.70% and acidity 0.26%. The presence of starch was detected in 6 (20%) of the cheese samples. For the fatty acid profile, it was observed that 83% of the cheeses and 50% of the butters had a percentage of linoleic acid above 3%, which is the average found in milk. Thus, it can be concluded that butter cheeses and bottle butters showed undesirable microbiological quality as well as the detection of fraud by adding starch and replacing milk animal fat with vegetable oil considering the high percentage of linoleic acid found in the samples